A Snapshot of Antimicrobial Resistance in Semi-Wild Oryx: Baseline Data from Qatar - Asma Mushahidur Rahman; Salma E. Ahmed; Shayma A. Osman; Radhia A. Al-Haddad; Abdallah Almiski; Ristha Kamar; Hana Abdelrahman; Issmat I. Kassem; Andrea Dogliero; Nahla O. Eltai (Antibiotics)
Background/Objectives: The spread of antimicrobial resistance (AMR) is a growing global health concern. Wild animals can play an important role in the amplification and dissemination of AMR and in conservation efforts aiming at controlling diseases in vulnerable wild animal populations. These animals can serve as reservoirs for antibiotic resistance genes and are key in the spread of AMR across ecosystems and hosts. Therefore, monitoring AMR in wild animals is crucial in tackling the spread of resistance in the environment and human population. This study investigated the phenotypic and genotypic resistance of Escherichia coli (E. coli) isolated from semi-wild oryx (Oryx leucoryx) in Qatar. Methods: One hundred fecal samples were collected from oryx in diverse natural reserves across Qatar. A selective agar medium was used to isolate E. coli, and the identity of the isolates was further confirmed using the VITEK® 2 Compact system. The Kirby–Bauer disk diffusion method was used to test antibiotic susceptibility. Genetic resistance determinants were identified through polymerase chain reaction (PCR) analyses and sequencing using the Oxford Nanopore Technology (ONT). Results: The results revealed that 18% (n = 18) of the samples harbored E. coli with resistance to a single antibiotic, 28% (n = 28) were resistant to at least one antibiotic, and 2% (n = 2) were multidrug-resistant (MDR). No resistance was observed against colistin. tetA and tetB encode tetracycline resistance were the most frequently detected genes (57.7%). Whole genome sequencing (WGS) was used to expand on AMR gene-PCR analyses and analyze the resistome of 12E. coli isolates. WGS identified several important antibiotic resistance determinates, including blaCTX-M-encoding Extended Spectrum Beta-Lactamase (ESBL) resistance, soxR associated with tetracycline target alteration, and mdtE, emrB, AcrE, mdtF, and marA related to ciprofloxacin efflux pump resistance. Conclusions: This study provides essential information regarding AMR in Qatari semi-wild animals, which will guide conservation strategies and wildlife health management in a world experiencing increasing antibiotic-resistant infections. Furthermore, these findings can inform policies to mitigate AMR spread, improve ecosystems, and enhance public and environmental health while paving the way for future research on AMR dynamics in wildlife.